Effect of polymer molecular weight on the electrospinning of polylactides in entangled and aligned fiber forms - Afifi, A.M.; Yamane, H.; Kimura, Y. (The Society of Fiber Science and Technology, Japan, 2010)
Thin fibers having diameters ranging from 25 nm to 2 mu m were successfully electrospun from solutions of polylactides (PLA) having different molecular weights both in entangled and aligned fiber forms. The latter aligned fibers were collected with a new target comprising a rotor around which several fins were attached. Low viscosity of the solutions resulted in formation of beads or beads-on-strings, while high viscosity gave homogeneous fibers at optimum conditions. The resultant aligned fibers were drawn to 2 - 3 times at various optimum temperatures. WAXD of the drawn fibers revealed smectic nature of the PLA chain arrangement in spite of crystal orientation supported. The mechanical properties of the PLA fibers were also improved after drawing.